Hubungan Tingkat Kecemasan dan Konsumsi Kafein pada Mahasiswa Semester Akhir - Dewa Dharma (STKIP Subang, 2025)
Final-year students often face high academic pressure, placing them at greater riskof experiencing anxiety. At the same time, consumption has become a commonhabit to enhance focus and energy during the process of completing a thesis orfinal project. This study aimed to examine the relationship between anxiety levelsand caffeine consumption among final-year university students. The studyemployed a quantitative method with a correlational design and involved 214students as participants. The instruments used were the Caffeine ConsumptionQuestionnaire–Revised (CCQ-R) and the State-Trait Anxiety Inventory Form Y-8(STAI-Y-8). The results indicated a significant positive relationship between anxietylevels and caffeine consumption among final-year students. This was evidencedby a Spearman correlation coefficient of r = 0.407 with p = 0.000, indicating thathigher levels of anxiety are associated with higher levels of caffeine consumption.